Manajemen Pendidikan Pesantren dalam Upaya Peningkatan Mutu Santri - Durroh Yatimah (Fak. Tarbiyah UIN Maliki Malang, 2011)
The research of cases study is aimed to describe and understanding indepth about the educational management in pesantren (Islamic boarding school) in the efforts of santries (Islamic student in pesantren) quality improvement in Madrasah Salafiyah III Komplek Q Krapyak Yogyakarta. The research of cases study is qualitative research that naturalistic kinds. The research technical’s used observations, indepth interviews, and documentations. Data analysis’s used data assemble, data display, data reduction, then some conclutions. The conclution of this research is functions of educational management in Madrasah Salafiyah III that first, there is educational planning in madrasah (Islamic school) still in learning planning around. Second, educational organizations in madrasah that covered in organization structure there are job descriptions, functions, be competent, task appropriates clearly to employees. Third, principals of madrasah as leader that institution is kyai (leader in pesantren) assistant to manage educational pesantren, so educational in madrasah can be effective. Fourth, educational controlling in madrasah is supervised, monitoring, and evaluation who principals apply by helped his subordinates. The efforts of santri quality improvement applying by madrasah as continue both to determine standard of santri quality, improving of management madrasah, and improving human resources that santri and ustadz (teacher in pesantren). Improving santri quality is take many programs like use entry test in madrasah, practice of teaching experiences, make science labor (end task), halaqah bahtsul masail al haditsah (discussion of studying up date problems), give the rewards to sanri’s achievement, khithabah (speech) fourth languages, dzibaiyyah (reads shalawat to Muhammad SAW prophet), tahlil, halaqah ta’lim, sorogan (private) kitab dan Quran, science daurah and tematic study. Programs of improving ustadz quality like workshop of asatidzs, discussions of ustadz studied, periode seminars, and make science labor.